Pengaruh Intensitas Bermain Game terhadap Konsentrasi Belajar Siswa SMK Al-Ikhlash Dalegan Panceng Gresik - Luki Filananoka; Ahmad Maujuhan Syah (Busyro : Jurnal Dakwah dan Komunikasi Islam, 2020)
Learning concentration is an ability to focus attention during the teaching and learning process. Disturbances in concentration in learning can be from many factors, both internal factors from within students and external environmental factors, one of these factors is the high intensity of playing online games. Playing online games for students who are too excessive can waste time in vain, so that it can result in students neglecting their main obligation, namely learning. If this goes on continuously and in the long term, it is estimated that students will experience addiction which has an impact on difficulty in receiving lessons due to disruption of student concentration when studying and thinking more about games than paying attention to the learning process. For this reason, this study was conducted to determine how much influence the intensity of playing online games has on learning concentration. This study aims to determine the level of intensity of playing online games by students at SMK Al-Ikhlash Dalegan Panceng Gresik and to determine the effect of the intensity of playing online games on students' learning concentration at SMK Al-Ikhlash Dalegan Panceng Gresik. This study uses a design with a quantitative approach. The population is 176 students of SMK Al-Ikhlash Panceng, the sample taken in this study is 20% of the population, namely 37 students. With data collection procedures in the form of questionnaires and documentation. Meanwhile, for the processing of the validity test data and the analysis technique using the product moment formula and simple linear regression formula. The results showed that the intensity of playing online games of students at SMK Al-Ikhlash Dalegan Panceng Gresik was in the "high" category with a percentage level of 37.8% of 37 students. The intensity of playing online games has a significant effect on the learning concentration of the students of SMK Al-Ikhlash Dalegan Panceng Gresik. The results of the study stated that the influence of the Intensity of Playing Online Games on Learning Concentration was 72.2%. with the value of Sig. shows a value of 0.000 which is smaller or below 0.05. which means that the intensity of playing online games has an influence on learning concentration.